Hungarian Monitoring, 20 September 1990 . [Magyar rádiófigyelő], 1990. szeptember 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Air embargo against Iraq - Polish Sejm debates modifying the constitution - Election dates set in Poland - Russian parliament dismissed Ryzhkov - Bundestag debate on unification - Week of diplomacy in Beijing Domestic Affairs: - Otto Habsburg visits the Gabčíkovo–Nagymaros dam construction site - Foreign ministers' meeting in Zakopane - Hungary's involvement in the Gulf crisis - Demonstration by Videoton employees Economy: - Mineral oil and vehicle gasoline imports - Details of the three-year economic plan - Whitehead on the acceleration of privatization - Rise in average wages - Rise in telephone tariffs Külpolitika: - Légi embargó Irak ellen - A Szejm alkotmánymódosításról tárgyal - Választási időpontok kitűzése Lengyelországban - Az orosz parlament leváltja Rizskovot - Bundestag-vita az egyesítésről - Diplomáciai nagyhét Pekingben Belpolitika: - Habsburg Ottó meglátogatja a nagymarosi építkezést - Külügyminiszteri találkozó Zakopanéban - Magyarország szerepvállalása az öbölválságban - Tüntetnek a Videoton dolgozói Gazdaság: - Kőolaj - És motorbenzin import - Részletek a hároméves gazdasági programból - Whitehead a privatizáció felgyorsításáról - Növekvő átlagkeresetek - Telefontarifák emelése